Calibration for ED-XRF profiling of coal cores for the Itrax Core Scanner. Issue 1 (20th October 2014) - Kelloway, Sarah J.; Ward, Colin R.; Marjo, Christopher E.; Wainwright, Irene E.; Cohen, David R.
<x content-type="archive" xml:space="preserve">Abstract</x> Recent developments in instrumentation mean that chemical analysis of large drill cores taken for geological purposes can be performed rapidly at sub-millimetre scales using core scanners equipped with energy-dispersive X-ray fluorescence spectrometers. The present study describes the development of a calibration for the Itrax Core Scanner (Cox Analytical, Sweden), intended for whole cores of coal-seam sections, without the need for sample preparation. The calibration was developed for key major elements (Al, Si, P, S, K, Ca, Ti, and Fe) based on pressed pellets of reference coals, allowing semi-quantitative and, at times, quantitative analyses. The influence of core curvature and surface roughness compared with an ideal flat-surface was also examined using model samples, and their influence on the apparent sample composition evaluated.